PELATIHAN PEMBAYARAN DIGITAL UNTUK MENSTIMULASI KEGIATAN BISNIS - Ekadjaja, Margarita; Theja, Amory Takahiro (Jurnal Serina Abdimas, 2023)
The growth in the number of internet technology users in Indonesia will certainly have an impact on increasing the number of users of various digital applications. The partner in this PKM activity is Tatajaya, which is an individual company that markets conventional sound system equipment at Glodok Plaza. The main problem for partners is the large number of old customers who want to make contactless payments and conduct online transactions. This is one of the causes for turning customers away to competitors who are more ready with digital transactions. The PKM Team's solution is to conduct training to provide information to partners regarding the digital payment process and the utilization of various digital payment platforms that exist today. The training was conducted offline and was divided into two sessions, namely a session on understanding the training material and a simulation session on using digital payment platforms to stimulate business. The material discussed includes an introduction to payment instruments in Indonesia, both cash and non-cash, the advantages and risks of using digital payment systems, and how digital payments work. The result of PKM activities is that partners can understand digital payment platforms such as e-wallets and are able to apply QRIS (Quick Response Code Indonesia Standard) as a digital payment instrument which is a cross between various digital payment platforms and mobile banking in Indonesia which can stimulate activities partner business. yang terjadi di Indonesia, berdampak kepada peningkatan jumlah pengguna berbagai aplikasi digital. Mitra pada kegiatan PKM ini adalah Tatajaya yang merupakan perusahaan perseorangan yang memasarkan perangkat sound system secara konvensional di Glodok Plaza. Permasalahan utama mitra adalah banyaknya pelanggan lama yang ingin melakukan pembayaran secara contacless dan melakukan online transaction. Hal ini merupakan salah satu penyebab berpalingnya pelanggan ke pesaing yang sudah lebih siap dengan transaksi digital. Solusi Tim PKM adalah melakukan pelatihan untuk memberikan informasi kepada mitra terkait proses pembayaran digital dan pemanfaatan berbagai platform pembayaran digital yang ada saat ini. Pelatihan dilakukan secara luring dan dibagi dalam dua sesi, yaitu sesi pemahaman materi pelatihan dan sesi simulasi pemanfaatan platform pembayaran digital dalam menstimulasi bisnis. Materi yang dibahas meliputi pengenalan alat pembayaran yang ada di Indonesia baik tunai maupun non tunai, keuntungan dan risiko dalam pemanfaatan sistem pembayaran secara digital, serta cara kerja dari pembayaran digital. Hasil dari kegiatan PKM adalah mitra dapat memahami mengenai platform pembayaran digital seperti e-wallet dan mampu mengaplikasikan QRIS (Quick Response Code Indonesia Standard) sebagai salah satu alat pembayaran digital yang merupakan lintas dari berbagai platform pembayaran digital dan mobile banking di Indonesia yang dapat menstimulasi kegiatan bisnis mitra